(untitled) (Acta Polytechnica CTU Proceedings, 2017)
Development of technology management and security, transmission and information systems allows the concept of process management and security of railways and organizing the operation of a new, as yet non-phase in a non-traditional way. Requirements for higher efficiency, accuracy and flexibility of the attractiveness of rail transport Connection in the integrated transport systems are a challenge for the railways. These requirements can be solved just by changing the concept and technology of the presented here as an ITS-R.